Design and Fabrication of Flying Robot - R. , Hariharan; R.J. , Golden Renjith Nimal (International Journal of Psychosocial Rehabilitation, 2019)
As it is very much suitable to have a monitor view of a restricted area, this work has been taken up to fabricate such a flying robot. This is a high-tech remote flying robot specially designed for surveillance and monitoring application in military. The robot has battery powered propeller engine with two channel Radio Frequency (R.F) remote control. A high resolution colour camera with high frequency range transmitter is equipped for surveillance monitoring. A powerful transmitter and receiver enable to monitor surveillance up to distance of around hundred feet, Remote control is provided to control the robot. `The base transmitter transmits the signal, the signal is captured by the receiver in the robot and the received signal is fed to the Microcontroller Unit (MCU) where the signal is separated and is fed to independent motor drive circuit connected to high speed Direct Current (D.C) motor. A high frequency video camera is used to capture the live pictures which are transmitted to the base through a separate antenna fixed in the robot. The base unit has a receiver that gives video output which can be viewed in the monitor. This robot can be used where man cannot perform the task such as capture enemies landscape, gun fire operation and surveillance. A camera is used to monitor the surrounding. The robot configuration includes control transmitters for flying model robot, wireless camera and modulator receiver.